Unraveling FATP1, regulated by ER-β, as a targeted breast cancer innovative therapy - Mendes, Cindy (2019)
The authors thank to Shinozuka Tsuyoshi from Daiichi Sankyo, Japan, for the supply of arylpiperazine 5k (DS22420314). The research was funded by IPOLFG, EPE (FAI 2017) and by iNOVA4Health - UID/Multi/04462/a program fnancially supported by Fundação para a Ciência e Tecnologia/Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement and by Fundação para a Ciência e Tecnologia (personal fellowship: PD/BD/128337/2017).